SEMANTIC CHANGES IN METAPHORS DURING TRANSLATION (Universal International Scientific Journal, 2026)
This thesis analyzes the semantic changes that occur in the process of translating metaphors. The loss, narrowing or expansion of the meaning of a metaphor when translating from one language to another, the replacement of a metaphor with another metaphor, and the semantic shifts that occur under the influence of cultural factors are scientifically covered. It is also analyzed that the different forms of universal conceptual metaphor, loss of imagery, cultural diversity, and the inability to determine the purpose of using metaphor are the main factors that cause problems in the translation of metaphors, based on examples taken from English and Uzbek.
Keywords: metaphor; translation; semantic change